Correlation of Crtc1/3-Maml2 fusion status, grade and survival in mucoepidermoid carcinoma. (May 2017) - Birkeland, Andrew C.; Foltin, Susan K.; Michmerhuizen, Nicole L.; Hoesli, Rebecca C.; Rosko, Andrew J.; Byrd, Serena; Yanik, Megan; Nor, Jacques E.; Bradford, Carol R.; Prince, Mark E.; Carey, Thomas E.; McHugh, Jonathan B.; et al.
Highlights: We calculated gene fusion rates in patients with mucoepidermoid carcinoma. This is among the largest mucoepidermoid carcinoma cohorts to date. Fusion status did not significantly associate with tumor grade or survival. In previous studies, fusion status prognosis was likely confounded by tumor grade. Further characterization of additional mutational drivers is needed. Abstract: Objective: Mucoepidermoid carcinoma (MEC) is the most common malignant tumor of the salivary glands. Tumor stage and grade have historically been important predictors of survival. An oncogenic CRTC1 - or CRTC3-MAML2 gene fusion has been identified in a number of MECs. Historically, these gene fusions have been associated with lower grade tumors and better survival. However, reported gene fusion rates and prognosis varies widely across studies, and have not controlled for tumor grade. We sought to identify gene fusion rates and outcomes in our cohort of MEC patients. Materials and methods: An IRB-approved retrospective cohort of patients with MEC was identified at the University of Michigan. Clinical, histologic, and outcome data was collected from medical records. RNA was isolated from formalin fixed paraffin-embedded tumor sections, and qRT-PCR was performed to identify CRTC1/3-MAML2 gene fusions. Sanger sequencing of qRT-PCR products was used to confirm gene fusions. Results: Overall, 90 patient MEC tumors were collected (58 low-grade, 25 intermediate-grade, and 7 high-grade). Gene fusions were identified in 59% (53/90) of tumors. On univariate and bivariate analysis, fusion status did not significantly associate with grade or survival. Conclusion: We have identified a high rate of CRTC1/3-MAML2 gene fusions in a large cohort of MEC. We do not identify any correlation between fusion status with tumor grade or survival. These findings suggest further characterization of MECs is needed before considering the CRTC1/3-MAML2 gene fusion as a prognostic biomarker. Additional genetic drivers may account for survival and grade in MECs.